Left Main Coronary Artery Embolus: Unusual Presentation of Papillary Fibroelastoma of the Aortic Valve - Raju, Vijayakumar (Texas Heart Institute, 2010)
The usual cause of left main coronary artery obstruction is atherosclerotic occlusion resulting from plaque rupture and subsequent thrombus formation. In previously reported cases, tumor embolization into the coronary arteries caused sudden death and was detected only at autopsy. Herein, we report an unusual presentation of cardiac papillary fibroelastoma of the aortic valve in a 62-year-old man. The fibroelastoma caused a left main coronary artery embolus and symptoms of acute coronary syndrome. The fibroelastoma was successfully excised during a valve-sparing surgical procedure. We believe that this is the 1st report of tumor embolization to the left main coronary artery—and in a living patient.